Influence of various irrigation systems on the growth and yield of Lettuce (Lactuca sativa L.) - Gonzaga, N. R.; Gonzaga, A. B. Jr; Octavio, R.; Pepito, S. L. A.; Batuigas, A. M. T.; Magallanes, J. N. (International Journal of Agricultural Technology, 2022)
Lettuce being dependent to water during its growth and development is very sensitive to water stress. Lettuce applied with drip irrigation produced the highest crown size (polar, equatorial), most number of leaves and highest yield of 23.42 and 24.33 t ha-1 for two cropping periods, respectively. There was no notable effect observed among the various irrigation type on disease incidence. Leafy-type lettuce achieved the maximum plant stand with 89.70% during the second cropping. Head-type obtained the highest marketable yield during the first cropping season of 23.61 t ha-1 but leafy-type exhibited the highest yield of 17.72 t ha-1 on second cropping. Relatively, leafy-type produced more marketable number of leaves. Drip irrigation improved lettuce yields but there was no consistent varietal effect. Therefore, drip irrigation could possibly enhance lettuce production as implied by its significant effects on the yield and yield components